Validation of theory-based models for the control of plasma currents in W7-X divertor plasmas. (28th October 2021) - Dinklage, A.; Fuchert, G.; Wolf, R.C.; Alonso, A.; Andreeva, T.; Beidler, C.D.; de Baar, M.; Gao, Y.; Geiger, J.; Jakubowski, M.; Laqua, H.; Marushchenko, N.; et al.
Abstract: A theory-based model for the control of plasma currents for steady-state operation in W7-X is proposed and intended for model-based plasma control. The conceptual outline implies the strength of physics-based models: it offer approaches applicable to future conditions of fusion devices or next-step machines. The application at extrapolated settings is related to the validity range of the theory model. Therefore, the predictive power of theory-based control models could be larger than for data-driven approaches and limitations can be predicted from the validity range for the prediction of bootstrap currents in W7-X. The model predicts the L / R response when density or heating power is changed. The model is based on neoclassical bootstrap current calculations and validated for different discharge conditions. While the model was found to be broadly applicable for conducted electron-cyclotron-heated discharges in W7-X, limits were found for cases when the polarization of the electron cyclotron heating was changed from X2 to O2-heating. The validity assessment attempts to quantify the potential of the derived model for model-based control in the operational space (density, heating power) of W7-X.